Desenvolvimento de um produto viável mínimo de um sistema de planejamento de recursos empresariais de estoque - Ferreira, Rosivan Cardoso (Brasil, 2023)
Automating manual processes can provide valuable insights to assist decision-making within an organization. With this improvement in mind, this project aims to implement a technological solution for inventory control in a hospitality and restaurant company. In collaboration with potential end-users, the problem was studied and a solution was devised. As a result of the research, there was an understanding of the inventory process, which enabled the creation of the system and subsequent availability and evaluation.